تقييم مستوى الطلاب باستخدام اختبار اليويو (Yo-Yo) للتحمل المتقطع "مستوى 2" وبعض الاستجابات الفسيولوجية لمادة اللياقة البدنية - عبدالله, شيلان صديق; احمد, هاوكار سالار; حسين, ته نيا حسن (Sulaimani Journal for Humanities, 2021)
The fitness lesson contains grades and units in academic and annual achievement. This requires a standardized and clear test in order for students to familiarize themselves with the mechanism of the fitness assessment process and how to place grades on the basis of specific criteria. This prompted researchers to use a standardized test such as the Yo-Yo test to assess the fitness level of athletes. The aims of the study were to: 1- Evaluate and test the fitness level of students who have the fitness subject according to the college curriculum. 2- Learn the differences between the pre and post tests for heart rate and maximum oxygen consumption. 3- Finding out if the Yo-Yo test "Level 2" is used as a tool to assess the fitness of students of the College of Physical Education, due to the absence of a comprehensive test or procedure to assess students' fitness level. The researchers used the experimental method because it is convenient with nature of the problem. Twenty-four students among sixty-six students (aged 19-21 years) of the College of Physical Education and Sport Sciences/University of Sulaimani 2018/2019 have participated in this study. The students ’fitness level was assessed and tested by using the “YO-YO” intermittent endurance “Level 2” test. The main conclusions as follows: 1- The students ’fitness level was assessed and evaluated through the Yo-Yo test, and on its light they obtained grades. 2- There are significant differences between pre- and post-test and for the favour of the post-test for total distance covered and the VO2max. 3- Use the physiological indicator as the heart rate in order to monitoring the intensity of performance and compare it with other variables. In regards with recommendations, and the main recommendations were; 1- lecturer, teachers, and fitness coaches should use and approve the Yo-Yo test in order to assess and evaluate the fitness level of athletes. 2- Use the heart rate index in order to monitor performance severity and compare it with other variables.